INTRODUCTION TO THE RECONSTRUCTION AND MODELING OF GRASS-DOMINATED ECOSYSTEMS - Wooller M.J.; Beuning K.R. (My University, 2002)
The Poaceae contains an ecologically and taxonomically diverse array of species (s10 000 species and 655 genera) whose distributions range from the warm tropics to within the Arctic circle. Grass-dominated biomes support a rich biological community of grasses in association with seasonal herbaceous £owering plants and limited drought and ¢re-resistant arboreal components. Grasses and their associated species within grassland ecosystems possess a broad array of physiologies and ecologies including variable quantum yield e¤-ciencies and adaptations to frequent disturbance (herbivory and ¢re). These ecosystems currently cover a substantial part of the Earth's surfaceand, because they are highly productive, play a vital role in modern biogeochemical cycles.